Bronchial Thermoplasty in Severe Asthma: Best Practice Recommendations from an Expert Panel - Bonta, Peter I.; Chanez, Pascal; Annema, Jouke T.; Shah, Pallav L.; Niven, Robert (Respiration, 2018)
Bronchial thermoplasty (BT) is a bronchoscopic treatment for patients with severe asthma who remain symptomatic despite optimal medical therapy. In this “expert best practice” paper, the background and practical aspects of BT are highlighted. Randomized, controlled clinical trials have shown BT to be safe and effective in reducing severe exacerbations, improving quality of life, and decreasing emergency department visits. Five-year follow-up studies have provided evidence of the functional stability of BT-treated patients with persistence of a clinical benefit. The Global Initiative for Asthma (GINA) guidelines state that BT can be considered as a treatment option for adult asthma patients at step 5. Patient selection for BT requires close collaboration between interventional pulmonologists and severe asthma specialists. Key patient selection criteria for BT will be reviewed. BT therapy is delivered in 3 separate bronchoscopy sessions at least 3 weeks apart, covering different regions of the lung separately. Patients are treated with 50 mg/day of prednisolone or equivalent for 5 days, starting treatment 3 days prior to the procedure. The procedure is performed under moderate-to-deep sedation or general anesthesia. At bronchoscopy a single-use catheter with a basket design is inserted through the instrument channel and the energy is delivered by a radiofrequency (RF) generator (Alair TM Bronchial Thermoplasty System). BT uses temperature-controlled RF energy to impact airway remodeling, including a reduction of excessive airway smooth muscle within the airway wall, which has been recognized as a predominant feature of asthma. The treatment should be performed in a systemic manner, starting at the most distal part of the (sub)segmental airway, then moving proximally to the main bronchi, ensuring that the majority of the airways are treated. In general, 40–70 RF activations are provided in the lower lobes, and between 50 and 100 activations in the upper lobes combined. The main periprocedural adverse events are exacerbation of asthma symptoms and increased cough and sputum production. Occasionally, atelectasis has been observed following the procedure. The long-term safety of BT is excellent. An optimized BT responder profile – i.e., which specific asthma phenotype benefits most – is a topic of current research.